Spontaneous very preterm birth in relation to social class, and smoking: a temporal-spatial analysis of routinely collected data in Aberdeen, Scotland (1985–2010) - McCall, SJ; Green, DR; Macfarlane, GJ; Bhattacharya, S (Oxford University Press, 2019)
Objective: To examine trends of spontaneous very preterm birth (vPTB) and its relationship with maternal socioeconomic status and smoking.